Effect of Flow Rate, Duty Cycle, Amplitude, and Treatment Time of Ultrasonic Regimens Towards Escherichia Coli Harbouring Lipase - W. S. A., W. Omar; Ahmad Ziad, Sulaiman; Azilah, Ajit; Y., Chisti; A. L. T. , Chor (IOP Publishing, 2017)
A full factorial design (FFD) approach was conducted to assess the effect of four factors, namely flow rate, duty cycle, amplitude, and treatment time of ultrasonic regimens towards Escherichia coli harbouring lipase. The 22 experiments were performed as the following values with six replicates of centre point: flow rate (0.1, 0.2, and 0.3 L/min), duty cycle (0, 20, and 40 ), amplitude (2, 6, and 10), and treatment time (10, 35, and 60 min). The FFD was employed as preliminary screening in shake flask cultivation to choose the significant factors (P< 0.05) for further optimisation process. In this study, zero duty cycle signified non-sonication of amplitude and no treatment time effect to the E. coli culture. Also, the designated flow rate and amplitude accordingly showed no effect towards the amount of dry cells weight (DCW). DCW1 was found significantly degraded after the exposure of high duty cycle and treatment time as other factors remained constant. Whereas for the lipase activity, no significant difference was observed in any main factors or interactions. Paired samples t-test confirms the result at a p-value of 0.625. This experimental study suggests the direct and continuous approach of sonication caused an adverse effect on the cells culture density.